Social work education in the face of the challenges of Brazilian higher education (Temporalis, 2026)
Grounded in the historical-dialectical materialist method, based on bibliographic and documentary research, this article analyzes the challenges of Brazilian higher education and its impact on Social Work education. The investigation draws on the author’s personal and collective experiences, articulated with the Student Movement and the struggles of professional entities, combined with the analysis of papers published in Revista Temporalis between 2012 and 2022. The text revisits the historical trajectory of Social Work education, highlighting the dispute of societal projects materialized within academia, the effects of the commodification of education and the expansion of distance learning, as well as collective resistance strategies, especially the defense of the ethical-political project and the Curricular Guidelines. The study points to the urgency of strengthening the struggle for a public, critical, and emancipatory education, articulated with broader processes of resistance against capitalism and its expressions.
Keywords: Social Work Education; Higher Education in Brazil; Ethical-political project